Smart city development with digital twin technology - Hämäläinen, Mervi (University of Maribor, 2020)
Growing urban areas are major consumers of natural resources, energy and raw materials. Understanding cities´ urban metabolism is salient when developing sustainable and resilient cities. This paper addresses concepts of smart city and digital twin technology as means to foster more sustainable urban development. Smart city has globally been well adopted concept in urban development. With smart city development cities aim to optimize overall performance of the city, its infrastructures, processes and services, but also to improve socio-economic wellbeing. Dynamic digital twins are constituted to form real-time connectivity between virtual and physical objects. Digital twin combines virtual objects to its physical counterparts. This conceptual paper provides additionally examples from dynamic digital twin platforms and digital twin of Helsinki, Finland.
Keywords: smart city; digital twin; urban development; technology; bled e-conference; digitalisation; intelligent systems; towns and cities; technology; simulation; urban design; Internet of things; innovations; information technology; twins; fi=Markkinointi|en=Marketing|